Investigating the presence of fetal trisomy 13, 18, and 21 in Pakistani Patients and its’ Computational Analysis - Safdar, Amina; Zhaira, Dua; Kousar, Sumaira; Javaid, Shehla (International Journal of Endorsing Health Science Research, 2022)
Background: Chromosomal aneuploidy due to meiotic non-disjunction is among the most significant and common causes of miscarriages in humans. The present study was conducted to investigate the presence of fetal trisomy 13, 18, and 21 in Pakistani patients and analysis of its risk factors. Methodology: Fetuses were diagnosed for trisomies between 10 and 16 weeks of gestational age via Chorionic Villus Sampling. Fetal DNA was extracted through the Chelex method. The presence of trisomies 13, 18, and 21 was screened through amplification of Short Tandem Repeats (STR) on chromosomes 13, 18, and 21, respectively. The STR alleles were resolved through polyacrylamide gel electrophoresis (PAGE) and silver staining. Results: It was found that out of 367 patients tested between 2012 and 2018, 3 (0.82%) had trisomy 13, 3 (0.82%) had trisomy 18, and 34 (9.3%) had trisomy 21. Down syndrome (Trisomy 21) was the most common trisomy in Pakistani patients as compared to 13 and 18 trisomies. Via R analysis, it is assessed that cousin marriages and mother's age contribute positively towards trisomy; nevertheless, the presence of these factors does not confirm the presence of trisomy for any chromosome. Conclusion: It was observed that the age of the mother, delayed conception, and family marriages are the contributory factors for this problem. However, the prevalence of Trisomy 21 (Down syndrome) in the Pakistani Population is far greater as compared to Trisomy 13 (Patau syndrome) and Trisomy 18 (Edward syndrome).